KETERTARIKAN MASYARAKAT PEGADUNGAN TERHADAP PENDALAMAN BAKAT BIDANG SENI SEBAGAI AKTIVITAS SEPULANG SEKOLAH - Joshua Christian Chandra; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2020)
Pegadungan area, West Jakarta is a housing settlement. As a residential area, this area has several educational facilities (schools). But to be able to grow and develop, other facilities are needed such as the development of talent in certain fields that can be visited after school hours. Thus the activities of children after school can be contained positively. At this time the deepening of talent and skills in an academic and non-academic field is one of the important factors in children's development. Besides, Pegadungan Village also has people who are professionals as traders and employees. Where most of the offices in Jakarta are located in the center of the city that has very heavy traffic, the people who work as employees also need a place to take a break from the office world. Through questionnaire methods and theories from the book